PENGARUH PENERAPAN MODEL PROBLEM BASED LEARNING BERBANTUAN MULTIMEDIA INTERAKTIF TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS VIII SMP NEGERI 13 PADANG - Septiyani, Ellin (Jurnal Edukasi dan Penelitian Matematika, 2023)
This research is useful to find out the increase in students' problem-solving abilities with the application of the Problem Based Learning (PBL) model supported by interactive multimedia compared to without applying this model. This research is a quasi-experimental study with a population of class VIII students of SMP Negeri 13 Padang for the 2022/2023 academic year. The sample is the experimental class and the control class which are drawn randomly. The experimental class is a class that applies the PBL model supported by interactive multimedia and the control class is a class that does not apply this model. The research instrument is an essay question that is used in the final test. From the results of the study it was explained that the implementation of the PBL model supported by interactive multimedia was able to improve students' mathematical problem solving abilities, as evidenced by the average score of the final test indicators of experimental class students higher than the control class, as well as the mathematical problem solving abilities of students whose learning using the PBL model was better than the mathematical problem solving abilities of students whose learning uses direct learning models. So it was concluded that the students' mathematical problem solving abilities in the experimental class were better than the control class so that the PBL model supported by interactive multimedia was able to improve students' mathematical problem solving abilities in the experimental class.Keywords– Problem Based Learning, Problem Solving Abilities, Interactive Multimedia